Udmurt Mad’ Song: Paradox of a Genre - Irina Nurieva (Journal of Ethnology and Folkloristics)
The genre system of Udmurt folk songs has been researched by scholars many times. The accumulation and publication of new folklore and ethnographic material requires reconsideration of the general concept and definition. The folklore of northern Udmurtia gives interesting material for the study of the origins of some genres and of their interconnections. For example, the researching of the Udmurt mad' song genre, which is associated with popular Udmurt and Russian songs today, within the overall context of the Udmurt genre system, and use of comparison materials from the Komi and Ob Ugrians, has lead to ideas about the magical character of this genre and its syncretism (the song fairytale, the song riddle, the song dialogue).